A Synthetic Approach and Antimicrobial Evaluation of Annulated Pyrimidine and Triazine Derivatives - Aly, A. A. (Current Organic Chemistry, 2009)
A smooth and rapid one step synthesis of novel pyrido[2',3':3,4]pyrazolo[1,5-a]pyrimidines 4a,b and 7, pyrido[2',3':3,4]pyrazolo[5,1-c]triazines10-12a,b, pyrido[3“,2“:4',5']thieno[3',2':4,5]pyrimido/triazino[1,6-a]benzimidazoles 15-20 in synthetically useful yields utilizing, 3-amino-4-phenyl-5-(saccharin-2-yl)-1H-pyrazolo[3,4-b]pyridine (3) were described. The structure assignment of the new compounds is based on chemical and spectroscopic evidence. Preliminary biological studies of some synthesized compounds showed promising antimicrobial activities.